Low-frequency response test device of electret condenser microphone - Erni Yudaningtyas; Achsanul Khabib; Waru Djuriatno; Zakiyah Amalia; Ramadhani Kurniawan Subroto (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2020)
Arterial pulse measurement using electret condenser microphone requires the standard to validate the value of the measurement. This standard requires the test device to reproducing the mechanical vibration to emulate the arterial pulse vibration. The main objective of this paper is to discuss the test device of electret condenser microphone using class A amplifiers and low-frequency loudspeaker. To validate this pulse measurement, this class a amplifier is examined under an experimental setup. The experiments showed that the device can be used as an alternative solution to generate the mechanical signal source to simulate the human arterial pulse.